Comparison of treatment outcome of conventional drillings, osteotomes, and Densah bur used in dental implant placement in the posterior maxilla - Nikhil R. Gharge; Harish Saluja; Anuj Dhadhich; Seemit Vinod Shah (Journal of Oral Research and Review)
Background: Implant placement in the posterior maxilla is challenging due to the poor quality of the bone and the reduction in vertical bone height that occurs after extracting posterior teeth. In implant dentistry, success rates, osseointegration, and primary and secondary stability are crucial. This study compares the three surgical techniques for implant placement in the posterior maxilla to achieve the better outcomes for the surgeon, patient, and implant stability. Methodology: This study was conducted with institutional ethical approval, and informed consent was obtained from all the participants. The inclusion criteria comprised patients aged between 18 and 60 years with edentulous maxillary posterior arches. A total of 60 patients were enrolled in the study and divided into three groups: Conventional, Densah Bur, and Osteotome techniques. Clinical follow-up was conducted over 6 months to assess the treatment outcomes. Results: In this study, 19 patients were in the conventional group, 22 in the Densah Bur group, and 19 in the osteotome group. No significant differences in implant stability or crestal bone loss were found among the techniques. The mean primary stability was 3.15 ± 1.57 for the conventional group, 3.52 ± 2.58 for the osteotome group, and 3.63 ± 1.55 for the Densah Bur group. The Densah Bur technique required the least time (9.86 ± 1.79 min), while the osteotome technique took the longest (20.52 ± 1.80 min). The mean torque values were 43.68 ± 7.78 Ncm for the conventional group, 42.95 ± 7.96 Ncm for the Densah Bur group, and 47.36 ± 7.70 Ncm for the osteotome group. Conclusion: All three techniques – conventional, Densah Bur, and osteotome – showed good clinical outcomes in a 6-month follow-up, with better implant stability in the osseodensification cases. The novel Densah Bur technique proves superior in enhancing bone density and achieving primary stability in implant placement, particularly in the posterior maxilla with limited bone height and width.